2011
DOI: 10.1080/00028487.2011.620489
|View full text |Cite
|
Sign up to set email alerts
|

Detectability of Estuarine Fishes in a Beach Seine Survey of Tidal Tributaries of Lower Chesapeake Bay

Abstract: Detectability, the probability of encountering a species at a sampling site, is often overlooked in fisheries research despite its potential to obscure inferences on habitat use and lead to biased estimates of abundance. We used occupancy models to explore factors affecting detectability and occupancy (Ψ), the probability that a species inhabits a site, for three fishes frequently captured in Chesapeake Bay seine surveys: young‐of‐the‐year (age‐0) striped bass Morone saxatilis, yearling Atlantic croaker Microp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Thus, abundance, occupancy, and gear vulnerability are likely dynamic through the larval stage. Our results suggest that ontogenetic changes during early life history stages influence detection probabilities and occupancy, as has been shown by other studies (Falke et al 2010;Williams and Fabrizio 2011). As a result, estimates of occupancy and detection probability may be improved if they are allowed to vary through space and time (MacKenzie et al 2003).…”
Section: Sampling Little Fish In Big Riverssupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, abundance, occupancy, and gear vulnerability are likely dynamic through the larval stage. Our results suggest that ontogenetic changes during early life history stages influence detection probabilities and occupancy, as has been shown by other studies (Falke et al 2010;Williams and Fabrizio 2011). As a result, estimates of occupancy and detection probability may be improved if they are allowed to vary through space and time (MacKenzie et al 2003).…”
Section: Sampling Little Fish In Big Riverssupporting
confidence: 83%
“…Detection probabilities of larval and adult fishes in lotic systems vary across species (e.g., Falke et al 2010;Peoples and Frimpong 2011;McManamay et al 2014) and in this study we found detection probabilities of larval fishes ranged from <0.1 to >0.9. Although occupancy modeling has been conducted for adult and juvenile fishes of many species in a large variety of systems (e.g., Burdick et al 2008;Williams and Fabrizio 2011;McManamay et al 2014), few examples of occupancy models exist for larval freshwater fishes (but see Falke et al 2010Falke et al , 2012. We suggest that detection probabilities of larval fish is greater than those for juvenile and adult fish because larval fish are likely more abundant (as a function of the high fecundity of most fishes) and are less able to avoid sampling gears.…”
Section: Sampling Little Fish In Big Riversmentioning
confidence: 90%
“…In recent years, statistical methods have been developed to estimate the probability of detecting species at occupied sites based on multiple site visits (MacKenzie et al., , ). This approach has provided valuable information for fisheries management, including describing species distribution for rare species (Albanese, Litts, Camp & Weiler, ; Albanese, Peterson, Freeman & Weiler, ), assessing habitat preferences (Falke, Fausch, Bestgen & Bailey, ), evaluating sampling protocols (Peoples & Frimpong, ; Williams & Fabrizio, ) and improving the precision of abundance indices (Pritt, DuFour, Mayer, Roseman & DeBruyne, ). Although site occupancy models have been applied to the sampling of larval or juvenile fishes (Falke et al., ; Pritt et al., ), none have used a long‐term monitoring data set that spans decades and is comprises over 20,000 individual sampling events.…”
Section: Introductionmentioning
confidence: 99%
“…& Frimpong, 2011; Williams & Fabrizio, 2011) and improving the precision of abundance indices (Pritt, DuFour, Mayer, Roseman & DeBruyne, 2014). Although site occupancy models have been applied to the sampling of larval or juvenile fishes (Falke et al, 2010;Pritt et al, 2014), none have used a long-term monitoring data set that spans decades and is comprises over 20,000 individual sampling events.…”
mentioning
confidence: 99%
“…Williams and Fabrizio, 2011;Kotwicki et al, 2015). Using the method presented in this study, such processes could be included in computations at the individual level.…”
mentioning
confidence: 99%